Vacuum technology - Roth, A. (Alexander) (North-Holland ; Distributors for the United States and Canada, Elsevier Science Pub. Co., 1990)
This third updated and enlarged edition includes about 350 new papers added to the previous list of references. The contents have been revised and updated in the areas of:Thermonuclear pumping; Throughput; Transmission probability; Electronic circuit simulation; Sorption on charcoal; Desorption from porous materials; Desorption from stainless steel, A1 alloys (outgassing rates); Ion bombardment (glow discharge) cleaning; Clay - type pumps; Turbomolecular pumps-improvements; Cryosorption; NEG (Nonevaporable getter) linear pumps; Standards for measurement of pumping speed (Recommended practice, test domes); Spinning rotor gauges; Quartz friction gauges; Increase of sensitivity of thermocouple gauges; Lubrication in vacuum; Calibration of diffusion leaks; Improvements in leak detection. Besides its role in educational activities, the book will also serve as a handbook for those working in this field, or in fields connected to Vacuum Technology.Comments from the press on the second edition:"A valuable reference work for undergraduate libraries ... well organized and clearly written and strikes an appropriate balance between completeness and attention to fundamentals. The index and references are unusually complete. Recommended." (Choice)"Roth's new book contains a comprehensive collection of information on rarefied-gas flow, physical and chemical phenomena associated with vacuum technology, the production and measurement of high vacuum and sealing and leak-detection techniques. One finds a wealth of equations, numerical examples, tables, graphs and monographs. The book is more a handbook than a source book of latest developments. It is suitable for teaching, but the wealth of organized data should also make the book highly useful to engineers ..." (Physics Today)